PERBEDAAN PERSEPSI MAHASISWA TERHADAP EFEKTIVITAS LINGKUNGAN PEMBELAJARAN ONLINE DAN OFFLINE: KAJIAN FAKULTAS KEDOKTERAN UNIVERSITAS ABDURRAB - Huda Marlina Wati; Yasinta Devi Harahap; Yulnefia Yulnefia (Collaborative Medical Journal, 2022)
Background: Covid 19 made the learning system that was originally carried out offline forced to be switched to learning with the online method. This change can affect the perception of students which will later affect the effectiveness of learning. This research was conducted with the hope that it can be an evaluation material in the application of online learning at the Faculty of Medicine, Abdurrab University. Objective: To find out the differences in students' perceptions of the effectiveness of online and offline learning environments in Abdurrab University School of Medicine students. Method: This study used design with a cross-sectional research design. The sampling technique was carried out by stratified random sampling on 147 students of the academic stage of the Abdurrab University Faculty of Medicine. The instrument used was a DREEM (Dundee Ready Educational Environment Measure) questionnaire consisting of 50 questions that were analyzed using paired t-test. Results: There is a significant difference (p-value 0.031) between the perception of the online learning environment and the offline at the Abdurrab University School of Medicine. Conclusion: The perception of students at abdurrab University's Faculty of Medicine shows that the offline learning environment is more effective than online learning in terms of the learning process and lecturers. Meanwhile, the online learning environment is more effective than offline learning in terms of learning atmosphere, academic achievement, and social environment.